Lipase‐catalyzed hydrolysis of (+, ‐)‐2‐(4‐methylphenyl) propionic methyl ester enhanced by hydroxypropyl‐β‐cyclodextrin. Issue 1 (26th July 2018) - Liu, Guangyong; Zhang, Panliang; Xu, Weifeng; Wang, Lujun; Tang, Kewen
Abstract: BACKGROUND: Enzymatic kinetic resolution is an attractive technology for production of enantiomerically pure compounds. The objective of this research is to investigate the enantioselective hydrolysis of (+, ‐)‐2‐(4‐methylphenyl) propionic methyl ester (2‐(4‐MP)PPAME) to ( + )‐2‐(4‐methylphenyl) propionic acid ((+ )‐2‐(4‐MP)PPA) catalyzed by enzyme in an aqueous medium. RESULTS: Lipase AY from candida rugosa (CRL) was screened as the best lipase. Novozym 435 IM and lipopan S BG show higher catalytic activity but the enantioselectivity is very low. By addition of hydroxypropyl‐ β ‐cyclodextrin (HP‐ β ‐CD) to the aqueous system, an increased substrate conversion of 45.28% was obtained, the high enantiomeric excess remaining compared with the conversion of 28.05% without HP‐ β ‐CD. Response surface methodology and central composite design were employed to model and optimize the reaction system. CONCLUSION: Under the optimal conditions including pH of 6.60, 12.5 mg mL −1 enzyme, 35 mmol L −1 HP‐ β ‐CD, 0.06 mmol substrate, temperature 39°C, agitation speed 400 rpm and 40 h reaction time, the substrate conversion was up to 40.32% and the optical purity of the product ( + )‐2‐(4‐methylphenyl) propionic acid was up to 95.22%. © 2018 Society of Chemical Industry